Sonolytic and sono-fenton pretreatment of waste activated sludge - Savun, Başak. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2011., 2011)
The pretreatment of waste activated sludge (WAS) to facilitate solubilization and biodegradability is most common using thermal, mechanical (e.g. ultrasound, high pressure homogenization), chemical (oxidation) and alkali methods. Ultrasonic disintegration is one of the most effective one owing to the capacity of ultrasound to break-up microbial cells and extract the intracellular material. The mechanism involves deagglomeration of biological flocs and disruption of large organic particles via the shear forces produced by high pressure waves during the implosion of cavitation bubbles. A less common method of WAS pretreatment is the Fenton process, in which the production and diffusion of hydroxyl radicals through the microbial cell membrane lead to the oxidative decomposition of the cell wall. Moreover, hydroxyl radicals are highly effective in oxidation of recalcitrant compounds in the sludge, the biodegradable products of which are further subject to biochemical treatment. The objective of this study was to examine the impact of low-frequency ultrasound (US) on disintegration and dewatering characteristics of waste activated sludge originating from municipal wastewater treatment plants, and to enhance the efficiency of the process by combining it with either the classical Fenton or an advanced Fenton process that utilizes metallic zero-valent iron powder instead of ferrous iron as the chemical reagent. The results of the study showed that pretreatment of WAS by short wave ultrasonic irradiation in the presence of Fe2+/H2O2 or Fe0/H2O2 is far more effective than each single process in terms of the degree of solubilization and bacterial inactivation. It was also found that US with the advanced-Fenton process was more efficient than US with the classical-Fenton, because closely equivalent yields were achieved by using a two-fold lower dose of hydrogen peroxide in the former. The finding was attributed to the power of ultrasound to disintegrate heterogenous surfaces, thus increasing surface defects and the number of active sites while inducing a continuous cleaning action.
Keywords: Sanitary microbiology.; Water -- Microbiology.; Sewage -- Microbiology.